Biofilm growth in a biological plate tower, BPT, for VOC air pollution treatment - Peixoto, J. (2002)
The growth of microorganisms in biofilters and biotrickling filters always leads to the occurrence of clogging. A good efficiency of removal makes it happen faster. To solve clogging and making that kind of process easy to operate steadily for a long time, a new concept of reactor was designed and tested with air polluted with toluene and Pseudomonas putida. The BPT is a cascade of plates to whose surface the bacteria attaches. Water flows down and air flows upwards. The reactor shows very good hydrodynamic performance and operates continuously without problem. When the thickness of the biofilm reaches the maximum value allowable, the set of plates is simply replaced by a clean one and the biomass is dealt with outside the reactor.